1985
DOI: 10.1002/hep.1840050210
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term maintenance of taurocholate uptake by adult rat hepatocytes co-cultured with a liver epithelial cell line

Abstract: Taurocholate (TC) uptake by adult rat hepatocytes co-cultured with other rat liver epithelial cells (RLEC) was studied comparatively to hepatocytes in primary culture. Cells were cultured on Petri dishes for desired times prior to measuring their ability to transport TC. TC uptake was linear for 150 sec in both culture conditions. In hepatocytes cultured alone, the initial rate of TC uptake at an extracellular concentration of 100 microM was 0.19 +/- 0.02 nmole per min per 10(6) cells after 48 hr of culture an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 16 publications
2
11
0
Order By: Relevance
“…A considerable step forward in long-term maintenance of differentiated hepatocytes was made by adding another liver epithelial cell type (126). When cocultured with rat liver epithelial cells probably derived from primitive biliary cells, hepatocytes from various species including humans survive for several weeks and retain various liverspecific functions; these include production of plasma proteins, expression of both phase I and phase II drug metabolizing enzymes, and taurocholate uptake (52,71,(127)(128)(129)(130)(131)(132)(133)(134)(135) (71,126,128) and with preservation of communication through gap junctions (136). These two features could be related because in pure hepatocyte cultures the addition of proteoglycans improves gap junction activity (137).…”
Section: However Survival and Metabolic Compe-mentioning
confidence: 99%
“…A considerable step forward in long-term maintenance of differentiated hepatocytes was made by adding another liver epithelial cell type (126). When cocultured with rat liver epithelial cells probably derived from primitive biliary cells, hepatocytes from various species including humans survive for several weeks and retain various liverspecific functions; these include production of plasma proteins, expression of both phase I and phase II drug metabolizing enzymes, and taurocholate uptake (52,71,(127)(128)(129)(130)(131)(132)(133)(134)(135) (71,126,128) and with preservation of communication through gap junctions (136). These two features could be related because in pure hepatocyte cultures the addition of proteoglycans improves gap junction activity (137).…”
Section: However Survival and Metabolic Compe-mentioning
confidence: 99%
“…Uptake studies with TCA were performed with the intact rat liver (Reichen and Paumgartner , 1975Hofman et al 1975;Dietmeier et al 1976;Kroker et al 1978aKroker et al , 1980Van Dyke et al 1982a;Poupon et al 1988), with isolated rat hepatocytes (Schwarz et al 1975;Anwer and Hegner 1978a;Schwenk and Schwarz t981;Eaton and Richards 1986;Kuhn and Gewirtz 1988;Schwarz and Watkins 1992), isolated skate hepatocytes Fricker et al 1987a;) cultured hepatocytes (Schwarz and Barth 1979;Scharschmidt and Stephens 1981;Van Dyke et al 1982b;Foliot et al 1985;F611mann et al 1990), and basolateral membrane vesicles (Inoue et al 1982;Ruifrok and Meijer 1982;Duffy et al 1983;Blitzer and Donovan 1984;Simion et al 1984a,b;Meier et al 1984;Suchy et al 1985Suchy et al , 1986Novak et al 1989). Uptake studies with GCA were reported with isolated rat hepatocytes Klaassen 1982b, Kuhn andGewirtz 1988).…”
Section: Carrier-mediated Uptake Of Conjugated Bile Acids Trihydroxy mentioning
confidence: 99%
“…This unfavorable situation is considerably improved if the hepatocytes are co-cultured with liver epithelial cell lines (Guguen- Guillouzo and Guillouzo, 1983;GuguenGuillouzo et al, 1983;Begue et al, 1984;Wegner et al, 1990). Co-cultivation not only prolonged the lifespan of the cultured hepatocytes, but also maintained their functional capacity and enhanced their response to various inducing agents (Clement et al, 1984;Lebreton et al, 1986;Foliot et al, 1985;Vandenberghe et al, 1988;Schrode et al, 1990;Wegner et al, 1990). There is increasing evidence that co-cultures are better suited for studies on the metabolism of xenobiotics than pure cultures of rat hepatocytes (Rogiers et al, 1990;Donato et al, 1991;Niemann et al, 1991;Akrawi et al, 1993;Coecke et al, 1993).…”
Section: Introductionmentioning
confidence: 99%